Plakoglobin expression and localization in zebrafish embryo development. (26th October 2004) - Martin, E.D.; Grealy, M.
Abstract : Plakoglobin (γ-catenin) and β-catenin are major components of the adherens junctions and can be localized to the nucleus by activation of the Wnt signalling pathway. In addition, plakoglobin is also found in desmosomes, a vertebrate-specific cell–cell adhesion structure. Plakoglobin expression and localization were examined at the protein level during zebrafish embryonic development by Western blotting and confocal microscopy. Plakoglobin was expressed throughout embryo development at the protein level. Western blotting revealed that embryonic plakoglobin protein content increased between 12- and 24-h post-fertilization (hpf). Confocal microscopy showed that at stages up to 12 hpf, plakoglobin and β-catenin were co-localized and expressed in both the nucleus and in cell–cell junctions. At 24- and 72-hpf, separate patterns were seen for plakoglobin and β-catenin. These data indicate that plakoglobin localization in the heart region shifts from adherens junctions to desmosomes during heart chamber development.